Phase II Study of Weekly Paclitaxel with Trastuzumab and Pertuzumab in Patients with Human Epidermal Growth Receptor 2 Overexpressing Metastatic Breast Cancer: 5‐Year Follow‐up. (2nd January 2019) - Wang, Rui; Smyth, Lillian M.; Iyengar, Neil; Chandarlapaty, Sarat; Modi, Shanu; Jochelson, Maxine; Patil, Sujata; Norton, Larry; Hudis, Clifford A.; Dang, Chau T.
Abstract: Background: Favorable progression‐free survival (PFS) and overall survival (OS) results were previously reported on a phase II trial of patients with human epidermal growth receptor 2 (HER2)‐positive metastatic breast cancer (MBC), treated with weekly paclitaxel in combination with trastuzumab and pertuzumab in the first‐ and second‐line setting, with a median follow‐up of 33 months. Here, we report updated PFS and OS results with more than 2 years of additional follow‐up. Materials and Methods: In this phase II study, adult patients with HER2‐positive MBC who received no or one prior therapy received intravenous paclitaxel (80 mg/m 2 weekly) with trastuzumab (8 mg/kg loading dose followed by 6 mg/kg every 3 weeks) and pertuzumab (840 mg loading dose followed by 420 mg every 3 weeks), administered in 21‐day cycles. Primary endpoint was 6‐month PFS, and secondary endpoints included median PFS and OS. Results: From January 2011 to December 2013, 69 patients were enrolled: 51 (74%) and 18 (26%) were treated in first‐ and second‐line metastatic settings, respectively. As of August 21, 2017, the median follow‐up was 59 months (range, 20–75 months; 67 [97%] patients were evaluable for efficacy). The 6‐month PFS was 86% (95% confidence interval [CI] 0.76–0.93). The median PFS was 24.2 months (95% CI 17–35) for the overall population; it was 25.7 months (95% CI 17.0 to not reached) and 20.1 months (95% CI 8.5–33.0) for patients with no and one prior treatment, respectively. The median OS was not reached for the overall group; it was not reached and 39.7 months (95% CI 32.9–66.7) for patients with no and one prior treatment, respectively. Treatment was well tolerated with no additional safety concerns. Conclusion: With a longer follow‐up of almost 5 years, combination of weekly paclitaxel, trastuzumab, and pertuzumab remains effective with a favorable median PFS and a median OS not reached. Abstract : The development of HER2‐targeted therapy has dramatically changed the outcomes of patients with HER2‐positive breast cancer. This article reports 5‐year outcome and toxicity data for patients originally enrolled in a phase II study evaluating the combination of weekly paclitaxel, trastuzumab, and pertuzumab for HER2‐positive metastatic breast cancer.